1991
DOI: 10.1038/bjc.1991.145
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical metastatic patterns of invasive lobular and ductal carcinomas of the breast

Abstract: Summary Seventy seven patients with metastases from an invasive lobular carcinoma of the breast have been compared with 72 consecutive metastatic ductal carcinomas. There was no difference in the metastatic free interval between the two groups. A distinct pattern of clinical presentation of metastases was seen; hepatic (P = 0.01) and peritoneal metastases (P =0.0003) occurred more commonly in lobular tumours. Bilateral cancers were more common in the lobular group (P = 0.01). No difference was seen in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
1
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 16 publications
7
36
1
4
Order By: Relevance
“…This finding helps to support the argument that less-aggressive tumour phenotypes are more likely to be associated with the development of bone metastases. In common with several previous studies, we found no evidence that patients with lobular carcinoma were more likely to develop bone metastases compared to patients with ductal carcinomas (Dixon et al, 1991;Fondrinier et al, 1997). Others have suggested that lobular carcinomas have a tendency to metastasise to bone (Borst et al, 1993;Sastre-Garau et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding helps to support the argument that less-aggressive tumour phenotypes are more likely to be associated with the development of bone metastases. In common with several previous studies, we found no evidence that patients with lobular carcinoma were more likely to develop bone metastases compared to patients with ductal carcinomas (Dixon et al, 1991;Fondrinier et al, 1997). Others have suggested that lobular carcinomas have a tendency to metastasise to bone (Borst et al, 1993;Sastre-Garau et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…As has also been previously demonstrated (Williams et al, 1986;Robertson et al, 1992), once a patient develops metastatic disease then neither the lymph node status nor the size of the primary tumour is relevant as predictors of survival. It is well known that the metastatic patterns of lobular and ductal carcinomas are different, with gastrointestinal and peritoneal metastases being more common in lobular carcinomas (Dixon et al, 1991). There has been debate in the literature as to whether tumour type has any bearing on the development of bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main prognostic discriminants is the site and number of metastases, which makes it difficult to compare (inter-) national data deriving from different hospitals. Nevertheless, median post-recurrence survival is mostly in the range of 18-24 months (Powles et al, 1980;Patel et al, 1986;Tomin & Donegan, 1987;Perez et al, 1990;Dixon et al, 1991), which strongly resembles our data (20.3 mo). Almost 60% of the women in the three hospitals had received radiation treatment for advanced disease.…”
Section: Discussionsupporting
confidence: 80%
“…Histological studies have found that lobular carcinoma metastasized to the same metastatic sites as ductal carcinoma; however lobular carcinoma frequently metastasized to unusual sites like the gastrointestinal tract, peritoneum, and adnexa [8][9][10][11][12]. In one of the earliest papers on the subject, all of the metastases to the stomach were infiltrating lobular cancer, and other papers had between 75-97% lobular histotype [13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%
“…In an autopsy study performed on 707 cases of metastatic breast cancer, the stomach was involved in 10% of cases, small intestine in 9%, and large intestine in 8%, with the peritoneum involved in 25% of cases. Overall, the gastrointestinal tract was involved in 16% of cases [6] A non-autopsy study done in 2005 at The Mayo Clinic showed that of 12,000 diagnosed with metastatic disease secondary to breast cancer, 73 (0.6%) were found in either the GI tract or peritoneum: esophagus (8%), stomach (28%), small intestine (19%), and colon and rectum (45%) [7].Histological studies have found that lobular carcinoma metastasized to the same metastatic sites as ductal carcinoma; however lobular carcinoma frequently metastasized to unusual sites like the gastrointestinal tract, peritoneum, and adnexa [8][9][10][11][12]. In one of the earliest papers on the subject, all of the metastases to the stomach were infiltrating lobular cancer, and other papers had between 75-97% lobular histotype [13][14][15][16] …”
mentioning
confidence: 99%